Covid-19 Health Protocol Compliance Based on Health Belief Model Approach in Kupang City - Mardianti, Melisa; Limbu, Ribka; Ndun, Helga J. N. (Media Kesehatan Masyarakat, 2024)
Health protocols have been established to prevent and control the transmission of COVID-19. However, some people still have not complied with implementing health protocols. This research aims to determine community compliance with the COVID-19 health protocol using the Health Belief Model (HBM) approach in Kupang City. This study uses a qualitative method with a phenomenological approach. Eight key informants and two supporting informants were determined using purposive sampling. The research results showed that informants felt vulnerable to infection because they interacted with other people and were outside the home for a long time. In contrast, other informants felt they were not worried about the spread of COVID-19. Informants comply with health protocols because they know the benefits of health protocols as preventing the spread of COVID-19, perceptions of the benefits of other health protocols, namely wearing masks to avoid pollution, washing hands, and using hand sanitizer to keep hands hygienic. The barriers identified were difficulty maintaining distance outside the home and discomfort when wearing a mask. Internal cues for informants to comply with health protocols are self-motivation because they are worried about the transmission and impact of COVID-19 and external cues in the form of appeals from the government and work demands. The role of health workers, government, and community leaders in educating about the importance of implementing health protocols by focusing on the benefits of health protocols and determining sanctions for those who violate compliance with health protocols.